Galvanocoagulation ecological sal method of current sewage treatment from ions of heavy metals - Vasilenko, Lesya; Vasilenko, Alexey (Київський національний університет будівництва і архітектури, 2017)
It implemented a general description of the washing waste water in electroplating. The analysis of existing methods of cleaning the wash wastewater containing heavy metal ions. The comparative characteristic and disadvantages of these methods are given. The method proposed galvanocoagulation engineering calculation of industrial filter for wastewater treatment from heavy metal ions, in which the galvanocoagulation process.
Keywords: wastewater; heavy metal ions; galvanocoagulation; filter loading.